Earth circuit of low pressure DC distribution net based on flexible direct current networking technology - ZHU JINDA; YANG SONGYING; LUO JIAN; WU DI; WEN CHUANXIN; LI HAOJIE; CHEN LUYAO; YU ZHUOFEI; LYU HONGSHUI; DONG CHANGCHENG (2017)
The utility model discloses an earth circuit of low pressure DC distribution net based on flexible direct current networking technology belongs to the power electronics field. The utility model discloses it inclines earth -freely through its direct current of alternating current filter directly grounded to set up earth circuit of low pressure DC distribution net based on flexible direct current networking technology to survey into the interchange of each VSC voltage source converter. The utility model discloses go into the ground current, keep wave filter efficiency based on the zero sequence of flexible direct current networking technology's low pressure DC distribution net restraining, promote stable state and trouble transient stability nature, to improve the fault recovery characteristic significant. 本实用新型公开了种基于柔性直流组网技术的低压直流配电网的接地电路，属于电力电子技术领域。本实用新型将基于柔性直流组网技术的低压直流配电网的接地电路设置为各VSC电压源变流器的交流测通过交流滤波器直接接地而其直流侧不接地。本实用新型对抑制基于柔性直流组网技术的低压直流配电网的零序入地电流、保持滤波器效率，提升稳态及故障暂态稳定性、改善故障恢复特性具有重要意义。